The Schooled Society Index: Measuring the Centrality of Schooling in the Twenty-First Century from a Global Perspective - Leandros Kavadias; Bram Spruyt; Toon Kuppens (Socius)
Since the end of World War II, a worldwide educational revolution has led to the development of what David Baker has termed schooled societies . In such societies, school-based education has become a central and authoritative institution, transforming individuals, groups and society at large. Up to this point, research on schooled society has focused mainly on its global similarities. Yet as within this global trend there exist important national differences, the theory of schooled society needs an indicator that can be used in empirical comparative research. Therefore, the authors develop a multidimensional index that maps cross-national differences in the centrality of schooling. The authors collected 12 indicators from internationally comparable country-level data to construct a unique and publicly available dataset containing 192 countries. Indicator reduction analyses indicated that two subdimensions could be identified: the “institutionalization of schooling” and “school-based allocation.” As these subscales were strongly related, the authors constructed a composite scale, namely, the Schooled Society Index. This index added value compared with classically used indicators of schooling. Finally, the authors study the relationships between the Schooled Society Index and a range of commonly used demographic, economic and political country-level variables.